Evaluation of Infrastructure Management of Solo’s Fort Vastenburg Heritage Building - Jayanto Iwa Dwi; Qomarun Qomarun (E3S Web of Conferences, 2024)
Surakarta is an old settlement in Indonesia that has many infrastructure heritages in the center of the city, one of which is in the form of soft infrastructure, namely the Vastenburg Fort building. This building has been neglected, even though it is listed as a national cultural heritage building and is protected by the cultural heritage law. The purpose of this research is to evaluate the existing of the cultural heritage building assets of Fort Vastenburg. This type of research is evaluation research with a qualitative approach. The process of collecting data by searching archives and documents of ownership of Fort Vastenburg assets and in-depth interviews with parties related to the management of cultural heritage management of fort buildings. The evaluation stage is carried out by measuring the suitability between the regulations of Law with empirical facts in the field. Furthermore, an assessment is carried out using qualitative analysis techniques, namely: reduction, presentation, and conclusion drawing or verification. The results showed that the land certificate owners of Fort Vastenburg amounted to 12. This makes it difficult for the Surakarta City Government to preserve the cultural heritage building of Fort Vastenburg, therefore the evaluation results are at a sufficient level.